A century of genocide : utopias of race and nation - Weitz, Eric D. (Princeton University Press, 2015)
"In a blend of gripping narrative and trenchant analysis, Eric Weitz investigates four of the twentieth century's major eruptions of genocide: the Soviet Union under Stalin, Nazi Germany, Cambodia under the Khmer Rouge, and the former Yugoslavia. Drawing on historical sources as well as trial records, memoirs, novels, and poems, Weitz explains the prevalence of genocide in the twentieth century-- and shows how and why it became so systematic and deadly"--Back cover